If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + 2x) + -6 = 30 Combine like terms: x + 2x = 3x 2x(3x) + -6 = 30 Remove parenthesis around (3x) 2x * 3x + -6 = 30 Reorder the terms for easier multiplication: 2 * 3x * x + -6 = 30 Multiply 2 * 3 6x * x + -6 = 30 Multiply x * x 6x2 + -6 = 30 Reorder the terms: -6 + 6x2 = 30 Solving -6 + 6x2 = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x2 = 30 + 6 Combine like terms: -6 + 6 = 0 0 + 6x2 = 30 + 6 6x2 = 30 + 6 Combine like terms: 30 + 6 = 36 6x2 = 36 Divide each side by '6'. x2 = 6 Simplifying x2 = 6 Take the square root of each side: x = {-2.449489743, 2.449489743}
| (X-5)2+(y-4)2=16 | | 7-3f^4=2 | | 5(2)+2-1=11-2(2) | | 7y-10=53 | | 44n=64n-2 | | 7y-15=46.74 | | (35/7)=-6x | | 2/3--11/3 | | X^2+9+27= | | 2a-b+120=180 | | 7y-15=32.39 | | 20/0/£400 | | X^2+9+27=37cm^2 | | 5xsquare+125=0 | | (2x-3)(2x^2-x+2)= | | 4b-7-3b+9= | | F(x)=0.05x^2-7x+300 | | 17x-(4x-(-6x+8)-1)+8=2x-(-12-(-12x+36)-1) | | 3(2x-7)-5(x-1)=0 | | x^2+y^2+2*x-6*y-15=0 | | M/18=1-/9 | | y=-1/2(2*x) | | 14/X=126 | | 16x+11y+6z=8 | | 2(x+4)=4+x | | (10/5)4x-15x | | 575758787585787+x=1 | | y=5x^2+30x-2 | | X^35=0.05 | | 3x+4y^2=0 | | 2x+8=2x+1 | | 12*7(3/8) |